Animals, Mimesis, and the Origin of Language - Kári Driscoll (Recherches Germaniques)
This essay takes a pivotal scene in Richard Wagner’s opera Siegfried, in which the eponymous hero attempts to communicate with a forest bird by imitating its song, as a point of departure for an exploration of Enlightenment theories of the origin of language, specifically those of Rousseau and Herder. The moment when Siegfried tries and fails to imitate the bird’s song represents a concurrence of themes from these earlier philosophical discourses and serves to elucidate how here, as in Rousseau and Herder’s accounts, animals are present at—indeed, seem to bring about—the origin of the very thing which later excludes them, namely language. Both Rousseau and Herder allude to the popular idea that the ﬁrst language was metaphorical, and for both the origin of language is the result of a mimetic encounter with an animal. In reading these accounts in conjunction with the Siegfried episode, I aim to show how imitation, indeed a specifically human failure of imitation, is the root of representation and thus ultimately of the human–animal divide itself.